2019
DOI: 10.1101/806299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sick plants in grassland communities: a growth-defense trade-off is the main driver of fungal pathogen abundance and impact

Abstract: Aboveground fungal pathogens can substantially reduce biomass production in grasslands. However, we lack a mechanistic understanding of the drivers of fungal infection and impact. Using a global change biodiversity experiment we show that the trade-off between plant growth and defense is the main determinant of fungal infection in grasslands. Nitrogen addition only indirectly increased infection via shifting plant communities towards more fast growing species. Plant diversity did not decrease infection, likely… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 88 publications
0
9
0
Order By: Relevance
“…In general, plant enemies might change plant functional composition by preferentially attacking faster growing, less defended plant species rather than slower growing, and more defended ones (e.g. Lind et al 2013;Kempel et al 2015;Cappelli et al 2019). Recent work on fungal pathogens in grassland has shown that plant species with a fast growth strategy are more likely to be infested by pathogens than species with a slow growth strategy (Cappelli et al 2019).…”
Section: Effects Of Plant Enemies On Plant Species Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, plant enemies might change plant functional composition by preferentially attacking faster growing, less defended plant species rather than slower growing, and more defended ones (e.g. Lind et al 2013;Kempel et al 2015;Cappelli et al 2019). Recent work on fungal pathogens in grassland has shown that plant species with a fast growth strategy are more likely to be infested by pathogens than species with a slow growth strategy (Cappelli et al 2019).…”
Section: Effects Of Plant Enemies On Plant Species Compositionmentioning
confidence: 99%
“…Lind et al 2013;Kempel et al 2015;Cappelli et al 2019). Recent work on fungal pathogens in grassland has shown that plant species with a fast growth strategy are more likely to be infested by pathogens than species with a slow growth strategy (Cappelli et al 2019). Communities consisting of fast growing species were also shown to be more strongly impacted by fungal pathogens (they lost more biomass) than communities consisting of slower growing species (Cappelli et al 2019), indicating that fungal pathogens consistently shift plant communities towards more slow growing, better defended species.…”
Section: Effects Of Plant Enemies On Plant Species Compositionmentioning
confidence: 99%
“…Plant pathogens are ubiquitous (Delgado‐Baquerizo et al ., 2020) and play a critical role in shaping plant communities and maintaining terrestrial ecosystem functions (Bagchi et al ., 2014; Cappelli et al ., 2020). As widely recognized in agricultural systems, plant pathogens can decrease photosynthesis (Fisher et al ., 2012), cause plant biomass losses (Allan et al ., 2010; Seabloom et al ., 2017) and plant mortality (Jia et al ., 2020), and ultimately reduce host plant fitness.…”
Section: Introductionmentioning
confidence: 99%
“…As widely recognized in agricultural systems, plant pathogens can decrease photosynthesis (Fisher et al ., 2012), cause plant biomass losses (Allan et al ., 2010; Seabloom et al ., 2017) and plant mortality (Jia et al ., 2020), and ultimately reduce host plant fitness. At the same time, pathogens tend to disproportionately affect dominant species through negative density dependence (Chen et al ., 2019) or growth‐defense trade‐offs (Cappelli et al ., 2020), and thus promote plant species coexistence (Mordecai, 2011; Bever et al ., 2015). Overall, it is important to understand the factors that determine pathogen abundance, and to be able to predict when and where specific diseases will emerge.…”
Section: Introductionmentioning
confidence: 99%
“…Both plant invasions and infectious diseases can afflict natural plant communities [1,2] by reducing plant diversity and biomass production [35]. Invasive species and disease outbreaks can co-occur in communities because the species are co-introduced, or because invasive species amplify disease transmission [6].…”
Section: Introductionmentioning
confidence: 99%